Severe Tracheobronchomalacia after Prolonged Intubation of Multitrauma Patient - V. G. Sams; C. M. Lawson; A. B. Shibli; D. A. Taylor; P. R. Branca (Case Reports in Surgery)
Tracheobronchomalacia is a condition with significant morbidity with many etiologies including iatrogenic ones and should be considered in critically ill ventilated trauma patients. We present a case of a multitrauma patient who had difficulty weaning from the ventilator after prolonged intubation followed by tracheostomy tube placement. We describe her presentation, diagnosis, and management provide and as well a discussion of the condition.